(untitled) (Web of Technology: Multidimensional Research Journal, 2025)
This study investigates the methods of reducing and optimizing transportation costs in automobile transport using logistics and digital modeling approaches. The article analyzes the structure of transportation costs, methods of route optimization, vehicle load consolidation, and the use of software tools for cost prediction and management. The results demonstrate that the application of logistics and digital modeling can significantly reduce fuel consumption, minimize delivery time, and improve the economic and ecological efficiency of transport systems.